2004
DOI: 10.1038/labinvest.3700159
|View full text |Cite
|
Sign up to set email alerts
|

Localization of heparanase in esophageal cancer cells: respective roles in prognosis and differentiation

Abstract: In this study, we examined the distribution of heparanase protein in 75 esophageal squamous cell carcinomas by immunohistochemistry and analyzed the relationship between heparanase expression and clinicopathological characteristics. In situ hybridization showed that the mRNA expression pattern of heparanase was similar to that of the protein, suggesting that increased expression of the heparanase protein at the invasive front was caused by an increase of heparanase mRNA in tumor cells. Heparanase expression co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 43 publications
10
65
1
1
Order By: Relevance
“…25,26 A number of studies have also reported the presence of heparanase in the nucleus of cells, [27][28][29][30] with nuclear heparanase being associated with a favorable prognosis and cytoplasmic heparanase with poor survival in patients with lung, neck and gastric cancers. 31 There is some evidence that nuclear heparanase expression is linked to cell differentiation 28,30,[32][33][34] but, despite such reports, the functional relevance of nuclear heparanase remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 A number of studies have also reported the presence of heparanase in the nucleus of cells, [27][28][29][30] with nuclear heparanase being associated with a favorable prognosis and cytoplasmic heparanase with poor survival in patients with lung, neck and gastric cancers. 31 There is some evidence that nuclear heparanase expression is linked to cell differentiation 28,30,[32][33][34] but, despite such reports, the functional relevance of nuclear heparanase remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that heparanase expression is induced in carcinoma of the esophagus. 18,20 Heparanase induction correlated with enhanced tumor cell invasion into the muscular and adventitia layers, increased tumor metastasis, and advanced tumor stage, altogether associated with poor survival. 18,20 High heparanase staining in esophageal adenocarcinoma biopsies noted in this study (Table 1) further supports this notion.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Heparanase induction correlated with enhanced tumor cell invasion into the muscular and adventitia layers, increased tumor metastasis, and advanced tumor stage, altogether associated with poor survival. 18,20 High heparanase staining in esophageal adenocarcinoma biopsies noted in this study (Table 1) further supports this notion. Interestingly, however, increased heparanase expression was already noted in Barrett's epithelium, representing the earliest stage of esophagus carcinogenesis (Table 1; Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations